2019
DOI: 10.21037/jtd.2019.11.14
|View full text |Cite
|
Sign up to set email alerts
|

The 100 most cited articles on thoracic surgery management of lung cancer

Abstract: Identification of the top 100 cited articlesBetween July and August 2018 , we performed a retrospective bibliometric analysis, identifying articles through the Web of Science (Thomson Reuters, New York, USA) which searches the Science Citation Index Expanded database, allowing access to over 12,000 peer reviewed journals and collected citation data published since 1945.Using selected key terms ("lung cancer", "surgery'", "lobectomy", "segmentectomy", "pneumonectomy", "wedge resection", "video-assisted thoracic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Web of Science (Thomson Reuters, New York, USA) allows access to more than 12,000 peer-reviewed journals published since 1945, along with their collected citation data [ 8 ]. On February 10, 2020, we searched online via all of the databases in Web of Science (including the Web of Science Core Collection, BIOSIS Citation Index, KCI-Korean Journal Database, MEDLINE, Russian Science Citation Index, and SciELO Citation Index).…”
Section: Methodsmentioning
confidence: 99%
“…Web of Science (Thomson Reuters, New York, USA) allows access to more than 12,000 peer-reviewed journals published since 1945, along with their collected citation data [ 8 ]. On February 10, 2020, we searched online via all of the databases in Web of Science (including the Web of Science Core Collection, BIOSIS Citation Index, KCI-Korean Journal Database, MEDLINE, Russian Science Citation Index, and SciELO Citation Index).…”
Section: Methodsmentioning
confidence: 99%
“…The bibliometric analysis on article type showed that these 100 most cited articles contained 79 original research articles (including 1 research letter), 10 guideline/ consensus/statement, 9 reviews and 2 commentaries. Among the original research articles, there was a higher proportion of RCTs (37.9%) than in other similar bibliographic analyses (Table 5) (17,31,32). These articles covered 10 topics related to lung cancer screening, with screening test effectiveness being the most frequent topic.…”
Section: Screening Riskmentioning
confidence: 97%
“…Web of Science (Thomson Reuters, New York, USA) allows access to more than 12,000 peer-reviewed journals published since 1945, along with their collected citation data [8]. On February 10, 2020, we performed a search online via all of the databases in Web of Science (including the Web of Science Core Collection, BIOSIS Citation Index, KCI-Korean Journal Database, MEDLINE, Russian Science Citation Index, and SciELO Citation Index).…”
Section: Search Strategy and Criteriamentioning
confidence: 99%